AN ECLOGITISED OCEANIC PALAEO-HYDROTHERMAL FIELD FROM THE ST. MARCEL VALLEY (ITALIAN WESTERN ALPS) - Martin, Silvana; Rebay, Gisella; Kienast, Jean-Robert; Mével, Catherine (Ofioliti, 2008)
The eclogite-facies Servette metaophiolites (St. Marcel Valley, Italian Western Alps) belong to the Piedmont Nappe. They are glaucophanite, chloriteschists, talcschists and associated mineralised quartzite derived from different types of hydrated Tethyan oceanic crust affected by sea-floor and sub-sea floor hydrothermal alteration. We first describe the geology and lithology of the Servette metaophiolites and their chemical signature, and then we focus on the estimation of the Alpine subduction-related peak P-T metamorphic conditions and associated microstructures. Estimation of the peak P-T conditions was performed via calculations of pseudosections representing the equilibrium assemblages in the studied rocks using THERMOCALC. These calculations yielded relatively uniform values for the high-pressure metamorphic equilibration, with temperatures of 550 ± 60°C and pressures of 2.1 ± 0.3 Gpa, higher than the previously estimated P-T in the St. Marcel Valley (T max = 500°C and P max = 1.4 GPa), but lower than those obtained in other localities of the Zermatt-Saas zone (T up to 550-600° C and P up to 2.5-3.0 GPa). Comparison with similar rocks from the Zermatt-Saas zone helps to constrain the peculiar conditions at the P peak of these hydrated rocks within the Alpine subduction slab.